Power, lift and drag coefficients analogy of wind turbine blade from aerodynamics characteristics of NACA2412 & NACA0012 - karthikeyan k v, R. Niranjan, Kumaravel.M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper analysis of two dimensional airfoils model of NACA002412 and NACA0012 for the aerodynamic characteristics at various Reynolds number for a range of attack from lift through stall, based on the chord length of the airfoil. Using the Spalart-Allmaras, the k-epsilon (RNG) and the k-omega shear stress transport (SST) models are used to simulate drag, pressure coefficient, local characteristics and the lift. In the wind tunnel of NACA(National Aeronautics Advisory Committee) experimental measurement and comparison prognosis for selected aerodynamic airfoils are presented. The geometric parameters of blade including twist angle distribution and chord are determined based on aerodynamic parameters results at a specific Reynolds number. This study is carried out by providing an optimal blade design strategy for horizontal-axis wind turbines operating at different Reynolds numbers. In this approach can be further developed to create the most efficient of horizontal axis wind turbine blade design. As a conclusion the experimental results were compared with simulation results, good concordance were noted